2014 Triennial Surveillance Review : Managing Director's Action Plan for Strengthening Surveillance. (Policy Papers; Policy Paper ;, 2014)
The 2014 review of surveillance comes at a critical juncture for the Fund and its member countries. Policymakers are navigating a brittle, uneven recovery that is still marred by the lingering effects of the crisis. They are also continuing to adapt to the challenges of a highly interconnected world, shielding their economies from potential negative spillovers while also striving to harness the benefits of globalization. It is imperative that Fund surveillance is positioned to help our members best chart this course. This paper presents specific proposals in the priority areas agreed in the 2014 Triennial Surveillance Review (TSR). These actions will help ensure that surveillance meets the current and future needs of the membership, and the wider global economic community.